GADGET SCREEN TIME USE OF STUDENTS IN SELECTED TERTIARY INSTITUTIONS: IMPLICATIONS IN THE NEW NORMAL LEARNING - John Mark R. Asio (Universitas PGRI Madiun, 2022)
Since the advent of the pandemic, students exposed to gadgets were even more dependent than ever before. This study aims to analyze tertiary students' gadget screen time usage during the pandemic. The proponent used a descriptive research via online survey as the primary data gathering tool. The study subjected the gathered data to statistical treatment. Results show that students responded that it is